Relationship between the religious attitudes of women with gynecologic cancer and mental adjustment to cancer. Issue 1 (February 2021) - Duman, Mesude; Durgun Ozan, Yeter; Doğan Yüksekol, Özlem
Abstract: Objective: This study was conducted to determine the relationship between religious attitudes of Muslim women with gynecologic cancer and mental adjustment to cancer. Methods: Designed as a descriptive relational study, this study was conducted with 123 patients with gynecologic cancer. A personal information form, prepared in accordance with the literature, the Religious Attitude Scale (RAS), and the Mental Adjustment to Cancer Scale (MACS) were used as data collection tools. The data were assessed using descriptive statistics, Pearson's correlation analysis, and linear regression analysis. Results: A positive correlation was determined between the RAS score and the fighting spirit subscale of the MACS ( r = 0.65, p < 0.001). A negative correlation was found between the helplessness/hopelessness and anxious preoccupation subscales of the MACS and the RAS score ( r = −0.40, p < 0.001; r = −0.30, p < 0.001, respectively). Significance of results: The present results are helpful in understanding the influence of religious attitudes on the mental adjustment to gynecologic cancer patients. The results can serve as a reference for nursing education and clinical healthcare practice. Palliative healthcare providers can participate in improved care by recognizing spiritual needs and by advocating for attention to spiritual needs as a routine part of cancer care.